Pengaruh Perbedaan Benih Asal Pertanian Organik dan Konvensional Terhadap Sifat Fisiologis dan Hasil Padi Organik Kultivar Lokal dan Unggul - Mildaerizanti, Didik Indradewa, dan Prapto Yudono (Jurnal Ilmu Pertanian, 2012)
ABSTRACTThe farmers involved in Organic farming have many problems, particularly in agriculture, in terms of the provisions dealing with the cultivation of organic food which refers to SNI 6729 in 2010 in which the seed used must come from organic farming itself. In addition to the seed, organic farming requires a suitable varieties for organic conditions, suspected nutrient deficiencies, while special varieties are produced  to organic land  is  not  yet  available.  Research  done “The Effect  of differences seed origin in organic and conventional farming on the physiological and yield organic rice of local cultivars (Mentik Wangi Susu) and superior (IR-64)". The research conducted at greenhouse K.P.   Tridharma Faculty of Agriculture. University of Gadjah Mada, Yogyakarta from March to August 2012. The research aimed (1) to  study the effect of seed to the physiological properties, and yield of organic rice on local varieties and superior (2) to determining a good seed for rice varieties organically grown. Research design by randomized block consist two factors with 5 replications, the first factor is the cultivar i.e. local cultivars (Mentik Wangi Susu (M)) and superior cultivars (IR 64 (I)), the second is the seed used i.e. the seeds of organic farming (O) and seeds of conventional (K).  Data  were  analyzed,  if  there  is  a  significant  difference  continued  with Duncant multiple range test at 5% level. The results showed that there was no differences between organic and  conventional   seeds to the physiological properties and yield of organic rice on local cultivars (Mentik Wangi Susu) and superior (IR 64). Local cultivars (Mentik Wangi Susu) has higher grain yield per hill than superior (IR-64).Key  words   :   organic   rice,   local   cultivar,   superior   cultivar,   physiological properties, yield